Polimorfisme gen ferroportin (FPN1) -1355 G/C sebagai faktor risiko anemia defisiensi besi pada ibu hamil - Nor Istiqomah; Sarah Safira Umarghanies; Arta Farmawati; Ahmad Hamim Sadewa; Yuliana Heri Soesilo; Kusumadewi Eka Damayanti; Dono Indarto (Jurnal Gizi Klinik Indonesia, 2013)
Background: According to WHO data, prevalence of anemia pregnancy in Indonesia is 44.3%, it’s higher than world prevalence (41.8%). Ferroportin (FPN1) is one of important iron exsporter for iron absorption, release, and recycle inside the body. The varian of FPN1-1355 G/C in promoter region, leads to increased of ferroportin expression and iron export, increased cellular iron needs, overexpression of soluble transferrin receptor (sTfR), decrease hemoglobin (Hb) and erythrocyte indices that manifest to iron deficiency anemia (IDA).Objective: This research will study the frequency of FPN1-1355 G/C polymorphism as a risk factor of IDA in pregnant women in Indonesia.Method: The research design was a case and control study. Blood samples were taken from 26 pregnant women with anemia and 48 pregnant women without anemia. FPN1-1355G/C polymorphism were determined using PCR-RFLP method. sTfR and ferritin level were measured with ELISA. Hemoglobin, erythrocyte indices, and sTfR level were compared among genotype group, then statistically analyzed using independent sample t-test and one way ANOVA. Bivariat analysis of Pearson test was conducted to analyze correlation between level of blood Hb and ferritin in pregnant women (p<0.05).Results: FPN1-1355 G/C polymorphism with frequency in pregnant women with IDA and in pregnant women with anemia non IDA were 100% and 95.2%, respectively (p=0.710; OR=1.600; 95%CI: 0.296-8.653). The mean of Hb level and erythrocyte indices in subjects carrying C allele were lower than subjects carrying only G allele although Hb level is not significantly different (p>0.05). The sTfR and hepcidin level in subjects carrying C allele were higher than subjects carrying only G allele (p<0.05). Conclusion: In this study the FPN1 gene promoter -1355 G/C polymorphism was not a risk factor for anemia, but it was a risk factor for iron deficiency anemia in pregnant women.